Socio-Economic Status and Life Expectancy in Lebanon: An Empirical Analysis - Audi, Marc; Ali, Amjad (Archives of Business Research, 2017)
This study has investigated the impact of socio-economic status on life expectancy in the case of Lebanon over the period of 1971 to 2014. Availability of food, CO2 emissions, secondary school enrollment, per capita income and population growth are used for reviewing socio-economic status of Lebanon. Johansen test is used for examining co-integration among variables. The results of Johansen co-integration show that there is co-integration among the variables of the model. The long run results of the model show that all selected independent variables of the model have significant impact on life expectancy in Lebanon. The causality test results reveal that all the independent variables have causal relationship with life expectancy at birth in the Lebanese case over the selected time period. The estimated results suggest that if government of Lebanon wants to increase life expectancy at birth, it has to improve its socio-economic status of its masses.